Facile one-pot synthesis of Cu x O/TiO2 photocatalysts by regulating Cu oxidation state for efficient solar H2 production - Rajendran, Sivaraj; Mani, Sunesh S.; Nivedhitha, Thazhath R.; Asoka, Anantha Krishnan; Arun, Pushkaran S.; Mathew, Thomas; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2023)
Development of highly efficient CuxO/TiO2 photocatalysts by regulating the oxidation state of Cu exclusively in either single or mixed oxidation state(s) is desirable but difficult to achieve without employing any external reagents. The present work describes a one-pot synthesis strategy to obtain CuxO/TiO2 photocatalysts with Cu in +1 and/or +2 by using a suitable combination of ethylene diamine tetra acetic acid (EDTA) and ethylene diamine, carefully varying the Cu content, and heat treatment process. CuxO/TiO2 nanocomposite catalysts were characterized thoroughly by physicochemical methods. Textural analysis indicates a high dispersion of CuxO on porous TiO2 with p-n heterojunctions between them in CuxO/TiO2 catalysts. UV-visible spectral analysis suggests the presence of CuxO on TiO2 with significantly extended absorption from the UV to the visible region. X-ray photoelectron spectroscopy (XPS) analysis indicates a strong synergetic interaction between TiO2 and CuxO due to the comparable CB potential and p-n heterojunction at the interface among them. Photoelectrochemical studies demonstrate excellent charge-carrier separation efficiency, low charge-transfer resistance, and high double-layer capacitance with Cu2O/TiO2 photocatalysts. Photocatalytic efficacy of a CuxO/TiO2 nanocomposite in thin-film form has been demonstrated for solar hydrogen generation in sunlight. The incorporation of Cu+ in TiO2 largely improves the H-2 production, and all of the CuxO/TiO2 nanocomposites in thin-film form exhibited higher efficiency compared to their particulate/suspension counterpart. Among the composite catalysts, TiCu-1 in thin-film form, with Cu exclusively in +1 oxidation state, exhibited a high hydrogen production rate of 7.06 mmol/hg, which is 6 times higher than its suspension counterpart; also catalysts containing mixed Cu-oxidation states exhibited about 60-70% activity as that of TiCu-1. The superior performance of Cu2O/TiO2 nanocomposites in thin-film form was due to their enhanced light harvesting ability, high mass transfer rate, and easy accessibility of the reactant species to the active sites.
Keywords: heterojunction; Photocatalysis; Solar hydrogen; thin film; titania

Bimetallic and plasmonic Ag and Cu integrated TiO2 thin films for enhanced solar hydrogen production in direct sunlight - Mani, Sunesh S.; Rajendran, Sivaraj; Arun, Pushkaran S.; Vijaykumar, Aparna; Mathew, Thomas; Gopinath, Chinnakonda S. (Energy Advances, 2024)
<div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle-integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation in sunlight. Integration of Ag + Cu on TiO2 significantly enhances the solar H2 production due to the combined SPR effect of both metal species and the possible synergistic interaction among Cu + Ag in Ag–Cu/TiO2. TiAgCu-1 (0.75 wt% Ag and 0.25 wt% Cu on TiO2) showed the highest H2 yield of 6.67 mmol h−1 g−1 and it is 43 times higher than that of bare TiO2. The thin-film form of TiAgCu-1 shows 5 times higher solar H2 production than its powder counterpart. 1 wt% of Ag or Cu on TiO2 shows a H2 yield of 4.6 or 2 mmol h−1 g−1, respectively, which underscores the importance of combined or synergistic effects. The increase in solar H2 generation in Ag–Cu/TiO2 is attributed to factors such as the SPR effect of Cu and Ag, and strong interaction between Ag and Cu. The high photocatalytic efficiency of the TiAgCu-1 thin film is attributed to the large dispersion of metallic species with relatively high Ag/Cu surface atomic ratio, enhanced light absorption, a heterogeneous distribution of Ag and Cu species, and high double layer capacitance. The inter particle mesoporous network increases the interfacial charge transfer and reduces the mass transfer limitations. The plausible photocatalytic reaction mechanism could involve the combination of direct electron transfer from metal (Cu/Ag) to TiO2 as well as the significant field effect due to the Ag–Cu alloy, which is expected to increase the electron excitation locally. <div class="abstract graphical" id="aep-abstract-id9" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Plasmonic metal nanoparticle integrated mesoporous TiO2 nanocomposites (Ag/TiO2, Cu/TiO2 and Ag–Cu/TiO2), prepared by a simple chemical reduction method, have been demonstrated to show superior activity in thin-film form for solar H2 generation.

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Multifunctional NiO/Ti3+–TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e− and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p–n heterojunction formation between NiO and Ti3+–TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+–TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni–Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+–TiO2 nanocomposites. EXAFS studies show that the Ni–O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+–O–Ti3+/Ti4+ lattice network. Ni2+/Ti3+–TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C–C cleavage of glycerol. The NiO/Ti3+–TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+–TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h−1 g−1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+–TiO2, formation of a p–n heterojunction at the interface between NiO and Ti3+–TiO2 and effective utilization of charge carriers for redox reactions.